Um olhar comparativo sobre a regulamentação dos veículos de mídia exterior urbana: os casos de São Paulo (cidade) e Roma | A comparative view of urban outdoor advertising (Out-Of-Home media) regulation: the cases of São Paulo (city) and Rome - Casarin, Vanessa; Martinelli, Raquel (InfoDesign, 2018)
O objetivo central deste trabalho é apresentar um estudo comparativo sobre como as cidade de São Paulo e Roma tem lidado em suas regulamentações com os diferentes suportes de mídia exterior urbana, uma vez que são estas normas que moldam com maior ou menor rigor a forma com que a informação de caráter comercial chega aos cidadãos. O desenho da informação depende, fundamentalmente, do suporte através do qual será veiculada. A mídia exterior tem um forte impacto na paisagem urbana e a partir da Lei Cidade Limpa implantada em São Paulo diversas cidades brasileiras se viram incentivadas a implantar ou alterar suas normativas neste sentido. A fim de contribuir com este fenômeno, procurou-se então estabelecer um paralelo entre a cidade de São Paulo, uma cidade de negócios, e a cidade de Roma, fortemente orientada ao turismo incentivado pelo seu profícuo patrimônio histórico, principalmente arquitetônico. No caso de São Paulo abordou-se o contexto de aplicação da regulamentação específica mais recente e suas alterações posteriores. Fez-se, a partir de uma analise documental da legislação vigente, uma comparação com a cidade de Roma. Observou-se que embora a cidade de Roma seja fortemente orientada ao turismo e a exploração da qualidade estética de sua paisagem, é mais permissiva em relação a presença de diferentes suportes de mídia exterior na paisagem urbana do que a cidade de São Paulo. ***** The main aim of this paper is to present a comparative study between the cities of São Paulo and Rome, and how these cities are dealing with different types of urban outdoor advertising (Out-Of-Home media) in its regulations since these regulations shape the way commercial information is placed in the landscape. The information design depends, mainly, on the support it will be placed. Outdoor advertising has a strong impact on the urban landscape. Since the Clean City Law was implanted in São Paulo, several Brazilian cities have been encouraged to implement (or modify) regulations in this sense. In order to contribute to this discussion, a parallel between the city of São Paulo, a business city, and the city of Rome, strongly oriented to the tourism encouraged by its historical heritage, mainly architectonic, are presented in this paper. The results shown consider only the documental analysis (of the normative legislation, maps, and publications pertinent to the subject) which formed the basis for the evaluation of the landscape, and not the evaluation of the landscape itself. It refers to the initial stage of the research. Its character is, therefore, descriptive and the comparison established between the different case studies aims to foment the discussion around the paths followed by the cities to deal with the spread and diversity of the OOH media nowadays. It was observed that although the city of Rome is mainly oriented to tourism and the profiteering of the aesthetic quality of its landscape, it is more permissive in relation to the presence of different types of OOH media in the urban landscape than the city of São Paulo.